Novel multi-targeted polymerase chain reaction for diagnosis of presumed tubercular uveitis - Sharma, Kusum (Springer, 2013)
BACKGROUND: The objective of this study was to report the use of multi-targeted polymerase chain reaction (PCR) in the diagnosis of presumed tubercular uveitis. Multi-targeted PCR using three targets specific for Mycobacterium tuberculosis, i.e., IS6110, MPB64, and protein b, was performed on intraocular fluid samples of 25 subjects. Nine had presumed tubercular uveitis, six had intraocular inflammation secondary to a nontubercular etiology (disease controls), and ten had no evidence of intraocular inflammation (normal controls). As described previously, response to antitubercular therapy was considered as the gold standard. RESULTS: Multi-targeted PCR was positive in seven out of nine patients with presumed tubercular uveitis and negative in all normal and disease controls. The sensitivity and specificity were 77.77% and 100%, respectively. For the diagnosis of presumed tubercular uveitis, multi-targeted PCR had a positive predictive value of 100% and a negative predictive value of 88.88%. CONCLUSION: Multi-targeted PCR can be a valuable tool for diagnosing presumed tubercular uveitis.